Complications of mammalian target of rapamycin inhibitor anticancer treatment among patients with tuberous sclerosis complex are common and occasionally life-threatening - Trelinska, Joanna; Dachowska, Iwona; Kotulska, Katarzyna; Fendler, Wojciech; Jozwiak, Sergiusz; Mlynarski, Wojciech (Anti-cancer drugs, 2015)
The aim of this study was to evaluate the most common adverse events (AEs) linked to everolimus therapy, a mammalian target of rapamycin (mTOR) inhibitor, in children and adolescents with tuberous sclerosis complex (TSC) hospitalized in one medical center. The study group included 18 patients with a diagnosis of subependymal giant cell astrocytoma or renal angiomyolipoma related to TSC. The median duration of therapy was 15 months. All clinical symptoms and laboratory abnormalities including complete blood count, fasting lipid profile, glucose level, and liver and kidney function tests were analyzed as potential AEs. The most common AEs of everolimus therapy were laboratory abnormalities (100% of patients) and infection complications (83 episodes in 15 patients). Infectious episodes of pharyngitis (67%), diarrhea (44%), stomatitis (39%), and bronchitis (39%) were the most common infections. They were mostly mild or moderate in severity (grade 1-2). In two cases, life-threatening conditions related to mTOR inhibitor treatment were encountered. The first was classified as grade 4 pleuropneumonia and Streptococcus pneumoniae sepsis, whereas the second was classified as death related to AE (grade 5) Escherichia coli sepsis. The most common laboratory abnormalities were hypercholesterolemia (13/18 patients - 72%) and hypertriglyceridemia (12/18 patients - 66%). Neutropenia (12/18 patents - 66%) and anemia (8/18 patients - 44%) were the most common hematologic toxicities. Everolimus treatment in TSC patients may lead to life-threatening outcomes, including sepsis and death. Long-lasting effects of everolimus treatment in the context of high incidences of different laboratory abnormalities found in TSC patients are another subject that should be researched further.